SURVEI MINAT BELAJAR SISWA TERHADAP PELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN DI SMP NEGERI 7 MUARO JAMBI - Icha Marisca; Reza Hadinata; Fitri Diana (LPPM STAI Muhammadiyah Probolinggo, 2025)
Interest is a source of motivation that drives them to do what they want when they are free to choose. When they see that something will be profitable, they feel interested, when satisfaction decreases, interest decreases. In SMP Negeri 7 Muaro Jambi, there are variations in student responses to PJOK learning, so a survey needs to be conducted to determine the extent of their interest in learning physical education, sports and health subjects. The design of this study is a descriptive quantitative study with a survey method with data collection techniques using questionnaires, sampling with a total sampling technique, which is aimed at all populations totaling 430 respondents. The calculation results show that students' interest in learning physical education, sports and health at SMP Negeri 7 Muaro Jambi on the indicator of feelings of pleasure is included in the high category with a percentage of 66%, which value is in the interval range between 61-80%, students' interest in learning physical education, sports and health at SMP Negeri 7 Muaro Jambi on the student interest indicator is included in the high category with a percentage of 64%, which value is in the interval range between 61-80%, students' interest in learning physical education, sports and health at SMP Negeri 7 Muaro Jambi on the student involvement indicator is included in the high category with a percentage of 70%, which value is in the interval range between 61-80%, students' interest in learning physical education, sports and health at SMP Negeri 7 Muaro Jambi on the indicator of attention in learning is included in the high category with a percentage of 70%, which value is in the interval range between 61-80%. The results of the calculation of students' learning interest in physical education, sports and health lessons at SMP Negeri 7 Muaro Jambi are included in the high category with a percentage of 67%, which is in the interval range between 61-80%.